2021
DOI: 10.1080/10530789.2021.1961990
|View full text |Cite
|
Sign up to set email alerts
|

Unsheltered homeless and unstably housed adults have higher levels of stress and more health risk factors than sheltered homeless adults

Abstract: Background: In the United States, approximately 568,000 individuals are homeless on a single night. Homelessness can be categorized into three subgroups: sheltered homeless, unsheltered homeless, and unstably housed. Few studies have examined the relations between homelessness subtypes, shelter service utilization, levels of stress experienced, and health risk factors. This study aimed to empirically examine whether shelter status the previous night was related to current stress, recent utilization of shelter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Participants with elevated blood pressure are likely facing barriers preventing them from obtaining a diagnosis of hypertension. Previous studies on older adult PEUH diagnosed with hypertension show they face numerous barriers to accessing disease monitoring and management services 6,9,12–14,19,20 . However, participants in these studies already have overcome a significant barrier to care compared to one‐third of our older PEUH cohort, as their hypertension was diagnosed.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Participants with elevated blood pressure are likely facing barriers preventing them from obtaining a diagnosis of hypertension. Previous studies on older adult PEUH diagnosed with hypertension show they face numerous barriers to accessing disease monitoring and management services 6,9,12–14,19,20 . However, participants in these studies already have overcome a significant barrier to care compared to one‐third of our older PEUH cohort, as their hypertension was diagnosed.…”
Section: Discussionmentioning
confidence: 88%
“…It is also important to consider hypertension rates in older adults experiencing unsheltered homelessness (PEUH) 8 . Studies that compare PEUH to shelter‐based PEH have found these two populations experience different health vulnerabilities 9–14 . For example, a study by Treglia et al 9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations